Microstructure stability of a fine-grained AZ31 magnesium alloy processed by constrained groove pressing during isothermal annealing - Fong, Kai Soon (2019)
In this study, an AZ31 magnesium alloy plate was processed by constrained groove pressing (CGP) under three deformation cycles at temperatures from 503 to 448 K. The process resulted in a homogeneous fine grain microstructure with an average grain size of 1.8 μm. The as-processed microstructure contained a high fraction of low-angle grain boundaries (LAGB) of subgrains and dislocation boundaries that remained in the structure due to incomplete dynamic recovery and recrystallization. The material's yield strength was found to have increased from 175 to 242 MPa and with a significant weakening of its initial basal texture. The microstructure stability of the CGP-processed material was further investigated by isothermal annealing at temperature from 473 to 623 K and for different time. Abnormal grain growth was observed at 623 K, and this was associated with an increased in nonbasal grains at the expense of basal grains. The effect of annealing temperature and time on the grain growth kinetics was interpreted by using the grain growth equation, Dn+Dn0=kt, and Arrhenius equation, k=k0 exp (−(Q/RT)). The activation energy (Q) was estimated to be 27.8 kJ/mol which was significantly lower than the activation energy for lattice self-diffusion (QL = 135 kJ/mol) and grain boundary diffusion (Qgb = 92 kJ/mol) in pure magnesium. The result shows that grain growth is rapid but average grain size still remained smaller than the as-received material, especially at the shorter annealing time.